2014
DOI: 10.1002/eat.22358
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and construct validity of the eating disorder examination‐questionnaire in college students: Further support for a modified brief version

Abstract: Objective The Eating Disorder Examination-Questionnaire (EDE-Q) is widely used in research studies across clinical and non-clinical groups. Relatively little is known about psychometric properties of this measure and the available literature has not supported the proposed scale structure. The current study evaluated the factor structure and construct validity of the EDE-Q in a non-clinical study group of young adults. Method Participants were 801 young adults (573 females, 228 males) enrolled at a large publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
220
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(253 citation statements)
references
References 38 publications
31
220
2
Order By: Relevance
“…Items are scored on seven-point scales. Subscales (Restraint, Overvaluation, Dissatisfaction) were internally consistent in earlier work, α=.89–.91 (45), and in the current study α=.89–.92. Additionally, EDE-Q items about ED behaviors were adapted for parent report.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Items are scored on seven-point scales. Subscales (Restraint, Overvaluation, Dissatisfaction) were internally consistent in earlier work, α=.89–.91 (45), and in the current study α=.89–.92. Additionally, EDE-Q items about ED behaviors were adapted for parent report.…”
Section: Methodssupporting
confidence: 89%
“…The EDE-Q retrospectively measures ED psychopathology over the past 28 days (44); we used a brief seven-item version of the full scale that demonstrates psychometric properties in nonclinical (45) and clinical (46) studies that are superior to those from the original measure. Items are scored on seven-point scales.…”
Section: Methodsmentioning
confidence: 99%
“…However, after the partial correlation analysis, the significant correlations with “Fear of Obesity” disappeared after controlling for “Self-Esteem Based on Shape and Weight”, whereas “Self-Esteem Based on Shape and Weight” remained significant even after controlling for “Fear of Obesity.” This result demonstrated that “Self-Esteem Based on Shape and Weight” is a factor conceptually distinct from “simple” body dissatisfaction such as that assessed via “Fear of Obesity”. These findings are confirmed by the studies of Hrabosky et al [22], Peterson et al [13], and Grilo et al [34], which emphasized the importance of the distinction between body image dissatisfaction and overvaluation of shape and weight with regard to the factor structure of the EDE-Q.…”
Section: Discussionsupporting
confidence: 74%
“…Hrabosky et al [22], Peterson et al [13], and Grilo et al [34] emphasized the importance of the distinction between “body image dissatisfaction” and “overvaluation of shape and weight” with regard to the factor structure of the EDE-Q. Hrabosky et al suggested that “overvaluation of shape and weight” appears to be a construct related to, but distinct from, “body image dissatisfaction.” In these studies, “overvaluation of shape and weight” is considered more pathological than “body image dissatisfaction,” and it therefore differentiates patients with eating disorders from normal controls [22].…”
Section: Introductionmentioning
confidence: 99%
“…Factor-analytic studies have demonstrated this distinction in BED (Grilo, Crosby, et al, 2010; Grilo, Crosby, & White, 2012), obesity (Grilo, Henderson, Bell, & Crosby, 2013; Hrabosky et al, 2008), and non-clinical (Grilo, Reas, Hopwood, & Crosby, 2015) samples. Previous research has documented an association of overvaluation with eating-disorder psychopathology severity and with self-esteem (Grilo, 2013).…”
Section: Discussionmentioning
confidence: 97%